The effect of dietary vitamin E on the pleopodal egg and stage-1 juvenile numbers of freshwater crayfish Astacus leptodactylus (Eschscholtz, 1823) - Harlioglu, MM; Barim, Ö (Elsevier, 2004)
The effect of vitamin E on the pleopodal egg and stage-1 juvenile number of freshwater crayfish, Astacus leptodactylus was investigated. Crayfish were fed daily 2% of their total wet weight with vitamin E supplemented diets and a control for 272 days. The vitamin E contents of the control diet, diet 1, diet 2, and diet 3 were 66, 100, 150 and 200 mg/kg, respectively, oil a dry weight basis. Vitamin E levels of the control and experimental diets were analysed by high performance liquid chromatography. Results showed that diet 1 containing 100 mg/kg supplemental vitamin E was associated with a significant increase (p<0.001) in the number of pleopodal eggs and stage-1 juvenile. In addition, the females fed with diet 1 produced significantly bigger pleopodal eggs (P<0.001). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Astacus; crayfish; pleopodal egg; reproduction; stage-1 juvenile; vitamin E